2010
DOI: 10.1007/s00520-010-1010-y
|View full text |Cite
|
Sign up to set email alerts
|

Family physician involvement in cancer care and lung cancer patient emotional distress and quality of life

Abstract: This study provides new knowledge on patients' emotional distress and QoL with cancer evolution and, particularly, their association with FP involvement. Other studies should be conducted to further explore FP role in cancer supportive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…The signing rate of family doctors with chronic diseases in rural areas of Shandong Province in the current study was approximately 28.9%. It was far lower than the target of 60% signing rate of key groups [ 13 ], and also lower than 67.6% signing rate in Eastern and Central Europe [ 28 ], which was consistent with previous studies [ 29 , 30 ]. It indicated that there was still a long way to push forward the FDCS among the vulnerable groups of the population in rural China.…”
Section: Discussionsupporting
confidence: 91%
“…The signing rate of family doctors with chronic diseases in rural areas of Shandong Province in the current study was approximately 28.9%. It was far lower than the target of 60% signing rate of key groups [ 13 ], and also lower than 67.6% signing rate in Eastern and Central Europe [ 28 ], which was consistent with previous studies [ 29 , 30 ]. It indicated that there was still a long way to push forward the FDCS among the vulnerable groups of the population in rural China.…”
Section: Discussionsupporting
confidence: 91%
“…Family physician services are favorably helpful in promoting HRQoL [20,40]-which was reconfirmed in this study showing that the EQ-5D-3L utility value among individuals who contracted with family physician services was greater than those who did not (P<0.001). HRQoL is a generic outcome measure to assess the effectiveness of interventions and a way of reflecting one's subjective perceptions and experiences [41].…”
Section: Discussionsupporting
confidence: 71%
“…In addition to the risk stratification for cancer patients, essential elements for shared care include improved communication between the general practitioner and oncologist [ 32 , 69 , 70 ]. It is equally important to provide patient-centred care, including engaging with patients and understanding their needs and preferences [ 71 ].…”
Section: Discussionmentioning
confidence: 99%